2008
DOI: 10.1007/s10552-008-9209-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risk of breast cancer among Latinas attending community clinics: risk comprehension and relationship with mammography adherence

Abstract: Objective To describe breast cancer risk perceptions, determine risk comprehension, and evaluate mammography adherence among Latinas. Methods Latina women age ≥ 35, primarily from Central and South America, were recruited from community-based clinics to complete in-person interviews (n=450). Risk comprehension was calculated as the difference between numeric perceived risk and Gail risk score. Based on recommended guidelines from the year data were collected (2002), mammography adherence was defined as havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 39 publications
4
52
0
7
Order By: Relevance
“…Other studies have affirmed this position. [19][20][21] The decision to remove the breast through preventive bilateral mastectomy among the high risk individuals has cosmetic, social, cultural and spiritual implications because it is a unique organ by virtue of its anatomical location, physiological role, role in sexuality, sociocultural and even spiritual function. 3,4 Despite outstanding benefit of preventive bilateral mastectomy, the procedure has its attendant consequences as women who have had removal of both breasts experienced varying degree of psychological effects and consequences on their feminine personality.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have affirmed this position. [19][20][21] The decision to remove the breast through preventive bilateral mastectomy among the high risk individuals has cosmetic, social, cultural and spiritual implications because it is a unique organ by virtue of its anatomical location, physiological role, role in sexuality, sociocultural and even spiritual function. 3,4 Despite outstanding benefit of preventive bilateral mastectomy, the procedure has its attendant consequences as women who have had removal of both breasts experienced varying degree of psychological effects and consequences on their feminine personality.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies in specific populations showed conflicting results: whereas Schumacher et al have found similar factors for worst adherence in American Indian and Alaska native people (6), Graves et al did not observe any association between the aforementioned factors and screening adherence in a sample of 328 Latinas living in the United States (12).…”
Section: Introductionmentioning
confidence: 99%
“…Perceived risk was assessed with one question that we used previously with Latinas, which asked women to report the likelihood that they would get breast cancer (definitely, very likely, somewhat likely, not likely, or unsure). 56 Subjective norms and attitudes included reported experiences of healthcare discrimination and perceptions of racism. Both items were previously validated in the African-American population, and to our knowledge, this was their first use among Latinos.…”
mentioning
confidence: 99%